THE PENNY AGAINST THE MILLION: THE ELECTION COVERAGE FOR THE CITY OF S. PAULO BY THE NEWSPAPER O ESTADO DE S. PAULO (1952-1953) - Fidelis, Thiago [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2016)
This article analyses the election for the city of S. Paulo in 1953 by the newspaper 0 Estado de S. Paulo, the highest circulation and the most influential periodic. Because of a federal law, a 30 years ago don't have election for Salo Paulo mayoral; when the law ended in 1952, there were two campaigns that polarized, the State Secretary of Health Francisco Cardoso and the state representative Janio Quadros. Supporting the first campaign, the newspaper has structured your news based on this perspective and its consequences will be analyzed here.
Keywords: Press History; O Estado de S. Paulo; Municipal Elections